2015
DOI: 10.1097/mao.0000000000000795
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Binding Epidermal Growth Factor-Like Growth Factor Heals Chronic Tympanic Membrane Perforations With Advantage Over Fibroblast Growth Factor 2 and Epidermal Growth Factor in an Animal Model

Abstract: Hypothesis That heparin binding epidermal growth factor like growth factor (HB-EGF) heals chronic tympanic membrane (TM) perforations at higher rates than fibroblast growth factor 2 (FGF2) and epidermal growth factor (EGF) in an animal model. Background A non-surgical treatment for chronic TM perforation would benefit those unable to access surgery or those unable to have surgery, as well as reducing the cost of tympanoplasty. Growth factor (GF) treatments have been reported in the literature with variable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…The animal models that have gained the most acceptance are the “infolding technique” (Amoils et al, ), and a newer model developed by Wang et al which uses topical dexamethasone and mitomycin along with ventilation tube insertion to generate chronic TMP in mice, this latter with a success rate of approximately 80% of non‐closure between 8 and 10 weeks (Wang et al, ). Additionally, Santa Maria et al () published three different mouse models of TMP using OSU8‐1 (a hydroxamate‐based metalloproteinase inhibitor that inhibits ligands that interact with epidermal grow factor receptors) (Umeda et al, ), obstructing the Eustachian tube and a model of chronic suppurative otitis media, reporting at least a 87.9% of patency of TMP after 3 months. One study demonstrates complete healing of all TMP within 4–6 weeks after using the infolding and thermal techniques (Emami et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The animal models that have gained the most acceptance are the “infolding technique” (Amoils et al, ), and a newer model developed by Wang et al which uses topical dexamethasone and mitomycin along with ventilation tube insertion to generate chronic TMP in mice, this latter with a success rate of approximately 80% of non‐closure between 8 and 10 weeks (Wang et al, ). Additionally, Santa Maria et al () published three different mouse models of TMP using OSU8‐1 (a hydroxamate‐based metalloproteinase inhibitor that inhibits ligands that interact with epidermal grow factor receptors) (Umeda et al, ), obstructing the Eustachian tube and a model of chronic suppurative otitis media, reporting at least a 87.9% of patency of TMP after 3 months. One study demonstrates complete healing of all TMP within 4–6 weeks after using the infolding and thermal techniques (Emami et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ideal animal models should mimic environments of compromised healing such as those resulting from long‐standing perforations and local infection. Animal models of delayed TMP have been recently described (Santa Maria et al, ; Santa Maria et al, ; Wang et al, ) showing varying results with controversy still existing on the minimal time of perforation patency to be considered clinically relevant. Authors have suggested that a patency period ranging from 8 to12 weeks is the minimum time for a perforation to be considered chronic (Truy et al, ; Deng et al, ; Santa Maria et al, ; Wang et al, ; Kuo et al, ).…”
mentioning
confidence: 99%
“…Local administration of HBEGF helps mice recover from chronic suppurative otitis media, a chronic inflammation of the middle ear 52 . Delivery of EGF or FGF2 was not effective 53 . It is unclear whether auto- or cross-induction (or both) of other ligands play a role in this process 54 , 55 .…”
Section: Aspects Of Individual Ligandsmentioning
confidence: 94%
“…2E-I (ii & iii)). This is a classic histological characteristic of a chronic TMP that has been described in the literature [3,6,9,12,37,45,50,51]. In acute TMP healing the epithelium would migrate across the perforation edge to bridge the defect, whereas in a non-healing chronic TMP, a stratified epithelial rim forms around the perforation edge which seems to act as a structural barrier impeding the migration of keratinocytes [6,52].…”
Section: Discussionmentioning
confidence: 97%